Body Mass Index and Amyotrophic Lateral Sclerosis: A Study of US Military Veterans - Mariosa, Daniela (Am J Epidemiol, 2017)
Amyotrophic lateral sclerosis (ALS) may be associated with low body mass index (BMI) at the time of diagnosis. However, the role of premorbid BMI in the development of ALS and survival after diagnosis remains unclear. In 2005–2010, we interviewed 467 patients with ALS from the US National Registry of Veterans with ALS and 975 frequency-matched veteran controls. In this sample, we evaluated the association of BMI and BMI change at different ages with ALS risk using unconditional logistic models and with survival after ALS diagnosis using Cox proportional hazards models. After adjustment for confounders, compared with a moderate increase in BMI between ages 25 and 40 years, stable or decreasing BMI was positively associated with ALS risk (odds ratio (OR) = 1.61, 95% confidence interval (CI): 1.20, 2.16). A 1-unit increase in BMI at age 40 years (OR = 0.95, 95% CI: 0.91, 0.98) but not at age 25 years (OR = 0.99, 95% CI: 0.95, 1.03) was inversely associated with ALS. These associations were similar for bulbar and spinal ALS but stronger for those with a delay of less than 1 year between symptom onset and diagnosis. We found no association between prediagnosis BMI and survival. A decreasing BMI from early to middle age and a low BMI in middle age may be positively associated with ALS risk.